Pulsatilla Decoction Can Treat the Dampness-Heat Diarrhea Rat Model by Regulating Glycerinphospholipid Metabolism Based Lipidomics Approach - Hua, Yong-li; Ma, Qi; Zhang, Xiao-song; Jia, Ya-qian; Peng, Xiao-ting; Yao, Wan-ling; Ji, Peng; Hu, Jun-jie; Wei, Yan-ming (Frontiers in Pharmacology, 2020)
Ethnopharmacological relevance Diarrhea is a major medical problem in clinical practice. According to the theory of traditional Chinese medicine (TCM), different types of diarrhea should be treated with different TCM formulations based on the targeted medical condition. Dampness-heat diarrhea (DHD) is a serious diarrheal disease and Pulsatilla decoction (PD), a traditional Chinese medicine, has been found effective against DHD. Objective The aim of this study was to clarify the mechanism of action of PD in DHD using an untargeted lipidomics strategy. Materials and methods The lipid biomarkers of DHD were selected by comparing the control and model groups using a colon lipidomics technology and an ultra-high performance liquid chromatography (UHPLC) coupled with Q Exactive plus mass analyzer. Multivariate statistical analysis and pattern recognition were employed to examine different lipids within the colon of PD-treated rats. Results The lipidomics profile of the model group were evidently disordered when compared to the control group. A total of 42 significantly altered lipids between the model-control groups was identified by multivariate statistical analysis. DHD may result from such lipid disorders which are related to glycerophospholipid metabolism, arachidonic acid metabolism and sphingolipid metabolism. After PD treatment, the lipidomic profiles of the disorders tended to recover when compared to the model group. Twenty lipid molecules were identified and some glycerophospholipids and arachidonic acid levels returned close to the normal level. Conclusions Glycerophospholipid metabolism may play an important role in the treatment of dampness-heat induced diarrhea using PD.